Typology of strategies used by University of the Philippines College of Dentistry clinicians in teaching patients in periodontics - Murjani, Bhabita V. (2005)
The manner by which dentists educate their patients is greatly influenced by training acquired in the university. A university's curricular program on patient education, whether implicit or explicit, plays a crucial role in honing the teaching skills of students, that is, in their ability to educate their patients in certain areas. Observing the actual practice of students as they educate their patients provides a glimpse of how the existing curriculum has been effective in honing their skills. The main objective of this study was to describe the various teaching strategies used by graduating dental clinicians in educating their patients in order to expose the strengths and weaknesses of the existing curriculum and thereby find ways by which the curriculum could be improved. This study involved the documentation of 47 patient encounters of the graduating clinicians in the Oral Medicine Section of the University of the Philippines College of Dentistry. Analysis was done to determine how clinicians educated their patients regarding plaque and its prevention. Recurring patterns in the manner of teaching, specifically in three elements of teaching - motivation, stimulation and patient involvement - were noted. Findings revealed that almost all clinicians performed patient education and employed a variety of teaching aids in the process. Four types of teaching strategies emerged from the study: the prescriptive, the elaborative, the responsive, and the evaluative. Though combinations of strategies were employed in each teaching element, dominance of a certain strategy was evident. The prescriptive approach was the most commonly employed strategy. In addition, the typology that emerged appears to have parallelisms to the cognitive taxonomy in terms of promoting different levels of learning. Teaching students these strategies could provide a concrete manner of improving their individual approach to patient education, encouraging them to bring patients to a higher level of learning, and increasing their sensitivity to matching teaching styles with learning styles. The end product of these improvements in training programs would result in the formation of a dentist who is more competent in teaching patients. Patients who are educated properly are more likely to return for treatment, comply with instructions, and maintain their oral health.
Thesis (Master in Health Professions Education)--University of the Philippines Manila.
Panel Members: Melflor A. Atienza MD MHPEd, Chair/Adviser; Erlyn A. Sana PhD, Reader/Critic; Danilo L. Magtanong DDM MHPEd, Member; Maria Lourdes Dorothy S. Salvacion DDM MHPEd, Member; Maria Cecilia D. Alinea MD MHPEd, Member.
Keywords: Patient education; Periodontics